Provenance in situ: Documenting Information of Origins Across GLAM Contexts. Issue 4 (1st October 2016) - Straughn-Navarro, Rachel
Column Editor's Notes: The "Advances in Library Data and Access" column examines technological advances internal and external to libraries. The focus is on how library data is created and used. The strength of the column is its broad, international focus and contributors are encouraged to explore issues and recent advances in information technology relevant to their geographical region, as well as the larger, global audience. Interested authors are invited to submit proposals and articles to the column editor at moulaisonhe@missouri.edu. Please include "IILR Submission" in the subject line of the email. ABSTRACT: Provenance information has become increasingly prioritized in cultural heritage institutions for economic and ethical reasons, yet definitions can vary from discipline to discipline. This column begins by examining a number of definitions of provenance, which focus on an object's chain of custody and are relevant to metadata creation in the cultural heritage sector. Additionally, the W3C Provenance Incubator Group created a new more inclusive schema (PROV) for documenting provenance information on the web. This column recommends a broadened understanding of provenance for information professionals, based on the work by the W3C, particularly as cultural heritage professionals seek to increase online access to digital objects.